Primary Tumor Resection and Survival in Patients with Stage IV Gastric Cancer - Müsri, Fatma Yalçin (J Gastric Cancer, 2016)
PURPOSE: The aim of this study was to determine whether surgical resection of the primary tumor contributes to survival in patients with metastatic gastric cancer. MATERIALS AND METHODS: A total of 288 patients with metastatic gastric cancer from the Akdeniz University, Antalya Training and Research Hospital, and the Meram University of Konya database were retrospectively analyzed. The effect of primary tumor resection on survival of patients with metastatic gastric cancer was investigated using the log-rank test. Kaplan-Meier survival estimates were calculated. Multivariate analysis was performed using Cox proportional hazards regression modeling. RESULTS: The median overall survival was 12.0 months (95% confidence intewrval [CI], 10.4~13.6 months) and 7.8 months (95% CI, 5.5~10.0 months) for patients with and without primary tumor resection, respectively (P<0.001). The median progression-free survival was 8.3 months (95% CI, 7.1~9.5 months) and 6.2 months (95% CI, 5.8~6.7 months) for patients with and without primary tumor resection, respectively (P=0.002). CONCLUSIONS: Non-curative gastrectomy in patients with metastatic gastric cancer might increase their survival rate regardless of the occurrence of life-threatening tumor-related complications.